Insecticide Susceptibility in Asian Honey Bees (Apis cerana (Hymenoptera: Apidae)) and Implications for Wild Honey Bees in Asia - Yasuda, Mika; Sakamoto, Yoshiko; Goka, Koichi; Nagamitsu, Teruyoshi; Taki, Hisatomo (Journal of economic entomology, 2017)
To conserve local biodiversity and ensure the provision of pollination services, it is essential to understand the impact of pesticides on wild honey bees. Most studies that have investigated the effects of pesticides on honey bees have focused on the European honey bee (Apis mellifera (Hymenoptera: Apidae)), which is commonly domesticated worldwide. However, the Asian honey bee (Apis cerana) is widely distributed throughout Asia, and toxicity data are lacking for this species. This study aimed to fill this important knowledge gap. In this study, we determined the acute contact toxicity in A. cerana to various pesticides, including neonicotinoids, fipronil, organophosphorus, synthetic pyrethroids, carbamate, and anthranilic diamide. Based on the test duration of 48 h of contact LD50 tests, A. cerana was most sensitive to dinotefuran (0.0014 µg/bee), followed by thiamethoxam (0.0024 µg/bee) and fipronil (0.0025 µg/bee). Dinotefuran is used extensively in Asia, thereby potentially creating a substantial hazard. More generally, A. cerana was approximately one order of magnitude more sensitive than was A. mellifera to most of the pesticides evaluated. The results of our study suggest that neonicotinoid pesticides should not be considered as a single group that acts uniformly on all honey bees, and that more careful management strategies are required to conserve A. cerana populations than A. mellifera.